Crystal structure and optical properties of fused-ring chalcone (E)-3-(anthracen-9-yl)-1-(4-nitrophenyl)prop-2-en-1-one - Zaini, Muhamad Fikri (Acta Crystallogr E Crystallogr Commun, 2019)
The title compound, C(23)H(15)NO(3), adopts an s-cis conformation with respect to the ethylene C=C and carbonyl C=O double bonds in the enone unit. The molecule is significantly twisted with a dihedral angle of 48.63 (14)° between the anthracene ring system and the benzene ring. In the crystal, molecules are linked into inversion dimers with an R (2) (2)(10) graph-set motif via pairs of C—H⋯O hydrogen bonds. The intermolecular interactions were analysed and quantified by Hirshfeld surface analysis. The molecular structure was optimized and a small HOMO–LUMO energy gap of 2.55 eV was obtained using the DFT method at the B3LYP/6–311 G++(d,p) level of theory. This value is in close agreement with the experimental value of 2.52 eV obtained from the UV–vis analysis. The crystal used was a two-component merohedral twin with a refined ratio of 0.1996 (16):0.8004 (16).